The patrons of the Kingdom. Shipowners, shipmasters, foreign merchants and the control of Sicily’s fiscal system at the beginning of the Trastamara age (1414-22) - Alessandro Silvestri (Reti Medievali Rivista, 2025)
In 1420, Alfonso V of Aragon (1416–1458), known as the Magnanimous, signed a legal contract with a group of patrons (i.e., shipowners and shipmasters) to secure ships for the royal fleet and military support to complete the conquest of Sardinia and launch an offensive against Corsica, then under Genoese rule. According to this agreement, the sovereign temporarily granted these patrons control over the kingdom’s most significant fiscal resources, namely, the revenues generated from grain and foodstuff exports through the sale of export licenses (tratte). The agreement also resulted in the transfer of extensive public authority from the Crown to the patrons, who gained direct administrative control over the ports, their personnel, and the castles located in the same port towns. After examining the reconstruction of the royal patrimony following Alfonso’s ascension to the Crown of Aragon in 1412, this essay explores Sicily’s role in financing the political and military agenda of Alfonso the Magnanimous, focusing on the agreement between the monarch and the consortium of shipowners and shipmasters. In this regard, it provides a detailed analysis of the contract’s contents, the distribution of fiscal resources among the patrons, and their social origins. Finally, the essay discusses Sicily’s increasing strategic and financial significance in supporting the Crown of Aragon’s subsequent campaigns in Naples and the Italian Mezzogiorno.